Interpreting the title: What is stored inside Anatole France’s L’Étui de nacre - Nikitina, Natalia A. (Вестник Томского государственного университета. Филология)
The title of a literary work is the first and, often, the last step into authorreader communication, be it a separate text or a collection. Sometimes its interpretation can be deliberately complicated by the author. This paper analyses the title of Anatole France’s cycle L’Étui de nacre as an example of such case. We argue that this title is cryptic and, in the absence of the author’s comments, needs interpretation from the reader. To understand the title and its function, we look at its both parts (étui and nacre) in the context of various discourses and traditions (myths, religions), paying special attention to France’s own works, in order to find a clue to the cryptic title. Although the image of a container could be used as a traditional metaphor for a collection of literary works, France’s choice of the lexeme makes this hardly conceivable as the word étui requires a complement which is missing from the title, so it is not known what the container is designed for, not to mention whether it is empty or full, open or closed, etc. Thus, the image of a container, important for France’s oeuvre, becomes significant in itself, as it continuously appears in all the parts of the cycle, acquiring several distinct meanings of keeping, secrecy, and memory. France also implies several ideas related to mother-of-pearl, being attracted by its aesthetic and literary associations, as well as its polysemy and ambiguity, the awareness of which is obvious from the analysis of his prose. The religious associations of the image that are often used to refer to Logos foreground the very idea of baptism and draw the reader’s attention to characters’ names in the cycle. Its mythological potential is realised differently in the parts devoted to different cultures ranging from Venus to Virgin Mary, and ultimately to the woman in general. Nacre also introduces the image of pearl, which France traces in Dante’s Divine Comedy, which, through a complex net of associations, embodies a universal verity comprised of numerous individual and often conflicting truths. The semes that are foregrounded in the cycle with the help of the title are those of whiteness and oscillation, with a background of meanings from several cultures. This is especially important for France, as the stories of L’Étui de nacre show the same objects or actions from different angles, and the author’s position is hardly conceivable. Both parts of the title can serve as references to myth and Christianity, as well as to several central concepts of the cycle, such as the complex nature of femininity, the relations between love and death, reason and faith, and the meaning of history. The intentionally elusive image implied by the title aims to reflect the ambiguity of these concepts, the unattainability of an ultimate and exclusive interpretation of the author’s position.